Pengaruh Pengetahuan Akuntansi, Pengalaman Usaha, Motivasi Kerja, Dan Skala Usaha Terhadap Persepsi Penggunaan Informasi Akuntansi Pada Pelaku UMKM (Studi Kasus UMKM Di Kecamatan Ujung Padang Kabupaten Simalungun) - Hendra Setiawan; Yenni Samri Juliati Nasution; Laylan Syafina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to assess the influence of various factors on the perception of information use among Micro, Small, and Medium Enterprises (MSMEs) in Ujung Padang District, Simalungun Regency. This study uses a quantitative approach with a convenience sampling method to collect data from MSME owners. Data analysis involves validity tests, reliability tests, normality tests, multicommenality tests, heteroscedasticity tests, partial tests, simultaneous tests and determination coefficient tests. Then this study uses multiple linear regression analysis techniques. The findings show that there is a significant influence of business scale, business experience, accounting knowledge, and work motivation on the perception of information use among MSMEs. However, about 56.7% of the variation in the perception of information use could not be explained by the variables studied, indicating the existence of other influencing factors. This study emphasizes the importance of improving the understanding and skills of MSME owners in utilizing accounting information and calls for collaborative efforts from various parties to support the sustainable development of MSMEs.